2018
DOI: 10.1155/2018/5405376
|View full text |Cite
|
Sign up to set email alerts
|

The Difference in Cervical Vertebral Skeletal Maturation between Cleft Lip/Palate and Non-Cleft Lip/Palate Orthodontic Patients

Abstract: Objective The aim was to evaluate differences in the cervical vertebral skeletal maturity of unilateral cleft lip and palate (UCLP) and non-cleft lip/palate (non-CLP) Saudi male orthodontic patients. Method This cross-sectional multicenter study took place at the dental school, King Saud University and King Faisal Specialist Hospital and Research Center, Riyadh, Saudi Arabia, between October 2014 and September 2015. The records of Saudi male orthodontic patients with UCLP (n = 69) were collected. Cervical vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 26 publications
0
25
0
Order By: Relevance
“…Development of children with facial clefts has been studied extensively, and several researchers report slowed tempos of bone development (Bowers, 2011;Batwa et al, 2018), and Figure 5. Plot of canine z-scores across age intervals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development of children with facial clefts has been studied extensively, and several researchers report slowed tempos of bone development (Bowers, 2011;Batwa et al, 2018), and Figure 5. Plot of canine z-scores across age intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Development of children with facial clefts has been studied extensively, and several researchers report slowed tempos of bone development (Bowers, 2011; Batwa et al, 2018), and dental maturation is delayed (Ranta, 1986; Mitsea and Spyropoulos, 2001), as well as somatic growth (Drillien et al, 1966; Ranalli and Mazaheri, 1975). Moreover, tooth size is diminished (Sofaer, 1979; Antonarakis et al, 2013) because enamel and dentin have virtually no reparative ability, so they forever reflect their environment during formation.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the growth spurt of these children should be awaited before conclusive results are formed concerning the measured cephalometric values regarding sagittal growth of the skeleton, since the results in patients in mixed dentition show a lot of variability. Regarding this concept, researchers should be aware of the fact that the end of growth in cleft children is later than in healthy noncleft children [24] .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that children with UCLP have delayed skeletal maturity. 11,31,32 Whether which may indicate that a link is present between the sella turcica and maxillary and mandibular growth. This however remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Bowers et al 16 found that children with UCLP tend to be shorter in stature. It has also been found that children with UCLP have delayed skeletal maturity 11,31,32 . Whether the dimensions of the sella turcica may vary in relation to the function of the pituitary gland remains an open question.…”
Section: Discussionmentioning
confidence: 99%